2015
DOI: 10.1523/jneurosci.1209-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

There and Back Again: Hippocampus and Retrosplenial Cortex Track Homing Distance during Human Path Integration

Abstract: Path integration, the updating of position and orientation during movement, often involves tracking a home location. Here, we examine processes that could contribute to successful location tracking in humans. In particular, we investigate a homing vector model of path integration, whereby a navigator continuously tracks a trajectory back to the home location. To examine this model, we developed a loop task for fMRI, in which participants viewed movement that circled back to a home location in a sparse virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
134
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 74 publications
13
134
0
Order By: Relevance
“…Such a result fits with research that has indicated that connections between the MTL and visuo‐spatial cortical areas serve several goal‐directed spatial navigation functions. Some of this work has provided evidence that cross‐talk between these regions is needed to code for visual cues (e.g., optic flow) present in the external world in service of forming a spatial map (Brown, Hasselmo, & Stern, ; Chrastil, Sherrill, Hasselmo, & Stern, ; Sherrill et al, ). Our results suggest that this relationship is present even when forming mental simulations of spatial representations.…”
Section: Discussionmentioning
confidence: 99%
“…Such a result fits with research that has indicated that connections between the MTL and visuo‐spatial cortical areas serve several goal‐directed spatial navigation functions. Some of this work has provided evidence that cross‐talk between these regions is needed to code for visual cues (e.g., optic flow) present in the external world in service of forming a spatial map (Brown, Hasselmo, & Stern, ; Chrastil, Sherrill, Hasselmo, & Stern, ; Sherrill et al, ). Our results suggest that this relationship is present even when forming mental simulations of spatial representations.…”
Section: Discussionmentioning
confidence: 99%
“…Using a novel loop closure task in 31 participants, Chrastil et al (2015) found that the hippocampus, RSC, para-hippocampal cortex and medial prefrontal cortex (mPFC) were recruited during successful path integration. Interestingly, in our results, the course of fiber tractography of the CB-II associates with all these brain regions, suggests a potential role of the CB-II in supporting path integration.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling also demonstrates how coding of spatial location and time can form a framework to form the associations necessary to link events to the spatiotemporal trajectory of an episodic memory [56,82]. Modeling of episodic memories as trajectories has inspired experimental tests of the coding of memory in humans [13,69,73]. However, a full understanding of the network dynamics for coding space and time in episodic memory will require both more sophisticated and detailed models as well as more explicit experimental tests of the different mechanistic components of these computational models.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent work showed that retrieval of a planned trajectory involves reactivation of intermediate locations on the trajectory [2]. Studies show coding of navigationally relevant information in fMRI activity, with hippocampus coding path length and entorhinal cortex coding the Euclidean distance to the goal [3,73]. Modeling shows how interaction of brain regions can allow performance based on semantic memory for the allocentric position of landmarks translated to the egocentric position of landmarks [45].…”
Section: Modeling Of Spatial Memory (Grid Cells Place Cells and Splimentioning
confidence: 99%
See 1 more Smart Citation